Training on the Development of Flipbook-Based Digital Teaching Materials to Improve Teacher Competence - Jayanti Syahfitri; Nasral; Pariyanto (Jurnal Pengabdian Sains dan Humaniora, 2026)
The transformation of 21st-century education requires teachers to possess adequate digital literacy competencies, particularly in developing innovative and interactive teaching materials. This Community Service Program aimed to enhance teachers’ ability to develop flipbook-based digital teaching materials using Canva and Heyzine applications. The program was implemented at SMP Negeri 29 Bengkulu Tengah, involving 15 teachers from various subject areas. The implementation method consisted of three stages: socialization, training and technology implementation, and evaluation. The results indicated a significant improvement in teachers’ understanding and technical skills in developing digital learning media. All participants successfully produced a flipbook aligned with their respective subjects and showed positive responses to the ease of using the applications. Overall, the program effectively strengthened teachers’ digital pedagogical competencies and supported more interactive learning aligned with the Merdeka Curriculum. Therefore, similar training activities should be carried out regularly and expanded to other schools so that more teachers can develop interactive digital learning media effectively